2017
DOI: 10.1136/thoraxjnl-2017-210177
|View full text |Cite
|
Sign up to set email alerts
|

Timing of onset of symptoms in people with idiopathic pulmonary fibrosis

Abstract: Little is known about when symptoms of idiopathic pulmonary fibrosis first develop. We identified incident cases of idiopathic pulmonary fibrosis-clinical syndrome (IPF-CS) from a UK primary care database and assessed the frequency of consultations for common symptoms in the 5 years prior to diagnosis. 1671 cases were identified with 5 years of data prior to diagnosis. Breathlessness was the most common symptom, followed by cough. Cases were significantly more likely than controls to experience these symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 8 publications
1
48
0
Order By: Relevance
“…9,10 Cough, dyspnea, and fatigue are frequently underrecognized in primary care, leading to delays in referral. 51,52 The use of generic PROMs and PREMs in primary care may bring dyspnea and cough to light, raising the suspicion and early detection of the disease.…”
Section: Early and Accurate Diagnosis With Patient-centered Educationmentioning
confidence: 99%
“…9,10 Cough, dyspnea, and fatigue are frequently underrecognized in primary care, leading to delays in referral. 51,52 The use of generic PROMs and PREMs in primary care may bring dyspnea and cough to light, raising the suspicion and early detection of the disease.…”
Section: Early and Accurate Diagnosis With Patient-centered Educationmentioning
confidence: 99%
“…If idiopathic pulmonary fibrosis (IPF) is to be cured, then it is likely that the "fibrosis" will need to be identified before it has led to widespread architectural destruction of the parenchyma. Unfortunately, by the time IPF is diagnosed, most patients have suffered symptoms for a number of years (1) and have considerable physiological abnormality, with reduced FVC and gas transfer (DL CO ) and irreversible loss of lung function (2). Therefore, step one on the path to cure IPF requires that early precursor lesions must be identified in presymptomatic individuals at a point at which the natural history can be positively altered.…”
Section: Yonis H Mortaza S Baboi L Mercatmentioning
confidence: 99%
“…Breathlessness is of major importance; an Australian idiopathic pulmonary fibrosis (IPF) registry study showed that breathlessness predicted quality of life explaining over 70% of the variation in the model 87. A primary care study showed increased consultations due to breathlessness by people, some up to 5 years prior to IPF diagnosis 88. The importance of breathlessness management in addition to ILD-directed treatment is emphasised in a recent consideration of chronic breathlessness as a new clinical syndrome, defined as disabling breathlessness, persistent despite optimised disease-modifying treatment 89.…”
Section: Palliative Respiratory Care In Ildsmentioning
confidence: 99%